Prevención de caídas: Estilos de vida y riesgo de caídas - Linda B. Bobroff; Jennifer Hillan (EDIS)
There are many things that may cause you to fall, and you can change several of these. This 1-page Spanish-language fact sheet describes some easy changes you can make to decrease your risk of falling. Written by Linda B. Bobroff and Jennifer Hillan and published by the UF Department of Family Youth and Community Sciences, May 2011.